2012
DOI: 10.1590/s0066-782x2012005000044
|View full text |Cite
|
Sign up to set email alerts
|

Oclusão do apêndice atrial esquerdo com o Amplatzer Cardiac Plug em pacientes com fibrilação atrial

Abstract: Results: All implants were guided by angiography alone. Procedural success was 99% (one patient suffered a cardiac tamponade requiring pericardiocentesis, and the procedure was waived). There were four major complications (the already mentioned cardiac tamponade, two transient ischemic attacks and one device embolization with percutaneous retrieval) and two minor complications (one pericardial effusion without clinical significance and one non-significant ASD evidenced at FU). There was one in-hospital death a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…In the registry of the PAC system, which contains the results achieved by skilled staff, the rate of pericardial effusion fell to 2.2% 74 and the same values were also reported in the subsequent PREVAIL trial 51 . The recent study performed by Tzikas et al 57 on the results achieved with the ACP device in more than 20 European and Canadian centres revealed a rate of pericardial effusion requiring drainage of 1.2%.…”
Section: Management Of Complicationsmentioning
confidence: 66%
See 1 more Smart Citation
“…In the registry of the PAC system, which contains the results achieved by skilled staff, the rate of pericardial effusion fell to 2.2% 74 and the same values were also reported in the subsequent PREVAIL trial 51 . The recent study performed by Tzikas et al 57 on the results achieved with the ACP device in more than 20 European and Canadian centres revealed a rate of pericardial effusion requiring drainage of 1.2%.…”
Section: Management Of Complicationsmentioning
confidence: 66%
“…For the current generation of the device, the depth of the LAA must be similar to the diameter to allow safe deployment. In the Panel’s experience this characteristic, which is apparently the device’s biggest drawback, has never prevented safe implantation, probably because several studies 74 have shown that as AF persists, LAA increase in size, generally with the same rate of expansion in their diameter and depth. However, if in doubt it is important to use the radiopaque markers provided on the deployment system which easily reveal the minimum device deployment depth.…”
Section: ‘Step By Step’ Proceduresmentioning
confidence: 99%
“…Being short, the ACP can be implanted in a shallow position in the LAA, as only the proximal 2 cm are needed for its occlusion. The occlusive disc permits the complete closure of the LAA orifice [59]. In a prospective randomized controlled trial by Holmes et al [60], with the intervention group consisting of 463 LAAC implantations, the most frequent primary safety event was severe pericardial effusion (defined as the need for percutaneous or surgical drainage).…”
Section: Pericardial Tamponade As a Results Of Left Atrium Appendage Omentioning
confidence: 99%
“…Observational studies with the ACP followed a regimen of clopidogrel + ASA for 1 month and acetylsalicylic acid for 3 to 6 months [ 60 ], borrowing the antithrombotic protocol from the experience with the Amplatzer PFO Occluder. In patients who are treated with antiplatelets drugs, it is reasonable to perform an imaging test (TEE or CT scan) before clopidogrel termination and again if ASA cessation is planned.…”
Section: Imaging For Left Atrial Appendage Occlusionmentioning
confidence: 99%